(untitled) (Huellas, 2021)
The main objective of the present article is to acknowledge the existence or absence of a marked leadership at a world level that allows for managing the threads of this pandemic which is taking place along the current year, a fact which can introduce changes into the international relationships in the near future. At the same time, some focal points of geopolitical tension which were generated by this global critical sanitary situation are identified. These could contribute to the debate about the transformation that many territories will experiment in a globalized-world framework with growing technological development and evident changes in the cultural standards coming about. To that end, an exploratory and descriptive methodology was used, which consisted in revising updated bibliography about the topic (scientific articles, reports, press reports and statistics coming from world-known international ?? organizations). It is concluded that the current coronavirus pandemic transformed the geopolitics into a multipolar disturbance to the point that, at present, the planet lacks an actor who can prove to be a leader able to manage this situation. In addition, multilateralism diminished and tense future relationships between China and the USA are foreseeable, being the Asian giant the one who might come out better off all this chaos.